International Mobility and Knowledge Exchange Between China and the West: A Study of Chinese Humanities and Social Sciences Scholars - Yuting Shen (沈裕挺) (ECNU Review of Education)
Purpose This study examines the impact of international academic mobility on knowledge exchange between China and the West, including its potential benefits and risks, specifically in the humanities and social sciences (HSS) fields. Design/Approach/Methods This study employed qualitative research methods; specifically, data were collected through interviews and analyzed using thematic analysis. Findings With increasing knowledge flows in global academia, Chinese HSS scholars are benefiting from international academic mobility. They engage in various activities, such as international visits, conferences, and research collaborations, and praise the role of mobility in building an understanding of Western culture and knowledge, including research dynamics, embodied and encultured knowledge, and location-specific textual materials. However, international mobility has inadvertently exacerbated global knowledge asymmetries, with some Chinese scholars uncritically adopting Western paradigms. Nonetheless, pioneering Chinese HSS scholars aim to promote a two-way knowledge exchange between China and the West by fostering cultural reflexivity and enhancing their global visibility. Originality/Value Chinese HSS scholars serve as an illuminating example in the context of global knowledge asymmetries dominated by the Anglo-American West. These findings have theoretical and practical implications for fostering equitable and inclusive knowledge exchange between Western and non-Western societies through international academic mobility.